2009
DOI: 10.1111/j.1540-8167.2008.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Duration of Atrial Fibrillation Detected by Continuous Monitoring: Crucial Implications for the Risk of Thromboembolic Events

Abstract: In patients with recurrent AF episodes, risk stratification for thromboembolic events can be improved by combining CHADS(2) score with AF presence/duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
252
2
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(275 citation statements)
references
References 40 publications
10
252
2
11
Order By: Relevance
“…An interesting observation supporting the hypothesis of a multivariable model and the absence of a fixed threshold predictive of increased risk is suggested from a proof-of-concept study in which the risk of stroke or TE events was found to be not only a function of the time spent in AF, but also of the baseline characteristics of the patients. 48 In this study, in patients with a high CHADS 2 score, even short episodes of AF significantly increased the rate of TE events; whereas in patients with a very low CHADS 2 score, even long episodes of AF did not.…”
Section: Af Burden and Risk Of Strokementioning
confidence: 44%
“…An interesting observation supporting the hypothesis of a multivariable model and the absence of a fixed threshold predictive of increased risk is suggested from a proof-of-concept study in which the risk of stroke or TE events was found to be not only a function of the time spent in AF, but also of the baseline characteristics of the patients. 48 In this study, in patients with a high CHADS 2 score, even short episodes of AF significantly increased the rate of TE events; whereas in patients with a very low CHADS 2 score, even long episodes of AF did not.…”
Section: Af Burden and Risk Of Strokementioning
confidence: 44%
“…И если мы сопостав-ляем данные о наличии и продолжительности запи-санных эпизодов ФП с показателями CHADS 2 каж-дого пациента, мы можем идентифицировать две группы пациентов, которые существенно отличаются по тромбоэмболическим профилям риска (0,8% про-тив 5%, p=0,035) (рис. 1) [9][10][11].…”
Section: сложности в определении групп риска больных с фпunclassified
“…The state of Goias, in central Brazil, has a CD prevalence higher than national average [3,6]. Furthermore, most of our patients lived in rural areas since an early age and were subsequently exposed to the CD vector.…”
Section: Recorded Parametersmentioning
confidence: 99%
“…The estimated cost of the combined medical and surgical treatment of an infected, pacemakerdefibrillator system in the United States was ∼$35,000 [6]. The resultant financial burden necessitates that a better understanding of the risk factors for PPM infection be achieved so that effective preventive strategies may be developed.…”
Section: Risk Factor Of Permanentmentioning
confidence: 99%